Sengenya dance music: its intrumental resources and performance - Darkwa, Asante (International Library of African Music, 2017)
Sengenya is a ceremonial dance of the Digo who live in Kwale District at the Coast province of Kenya. The Digo are one of the nine Bantu groups of coastal people - the Giriama, Duruma, Wachonyi, and others - who form the Mji Kenda cluster (of people). Like many traditional dances in the Digo area, Sengenya is performed by men, women and girlsjoined together in formally institutionalised social groups, with officers, by-laws, etc. Sengenya is performed mostly during the celebration of harusi ya kuoa (wedding ceremonies), national days, end of Ramadhani and on other occasions, like harambee (fund raising) meetings and barazas, which call for the performance of traditional music and dance for entertainment.
Keywords: African Music